THU0738-HPR Promoting physical activity in rheumatoid arthritis: developing a theory-based behaviour change intervention. (15th June 2017) - Larkin, L; Fraser, A; Gallagher, S; Kennedy, N
Abstract : Background: Physical activity has numerous benefits for people who have RA, however interventions targeting physical activity behaviour in people who have RA have had limited efficacy [1]. Objectives: To develop a theory-based behaviour change intervention to promote physical activity in people who have RA. Methods: Development was guided by the UK's Medical Research Council Complex Interventions framework [2] and consisted of three components; 1. Narrative review which explored the use of behaviour change theory in previous interventions 2. Systematic review which examined the content and structure of previous interventions 3. Qualitative study which explored the preferences of key stakeholders (people who have RA and health professionals) about the design of the intervention. Results: Previous interventions lacked consideration of behaviour change theory in design and delivery, and there was a large degree of variance in content, structure and delivery. Lack of knowledge of current physical activity recommendations for people who have RA was highlighted in the qualitative study, and delivery preferences were identified. Intervention development was mapped to the Behaviour Change Wheel [3] and employed the Theory of Planned Behaviour as it's theoretical basis. The proposed intervention is outlined in Table 1 . Conclusions: We have developed a theory-based intervention which considers the preferences of key stakeholders. Future research will determine the feasibility and effectiveness of this intervention. References: Larkin et al (2015) Behaviour change interventions to promote physical activity in rheumatoid arthritis: a systematic review. Rheum Intl 35(10):1631–40. Craig et al (2008) Developing and evaluating complex interventions: new guidance, BMJ (Clinical research ed.), 337, a1655. Michie et al (2014) The Behaviour Change Wheel: A Guide to Designing Interventions., Silverback Publishing: Great Britain. Disclosure of Interest: None declared